2020
DOI: 10.21203/rs.3.rs-18300/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude of metabolic syndrome and its components among adult residents of Mekelle city, Northern Ethiopia, community-based cross-sectional study.

Abstract: Background: Metabolic Syndrome is becoming a big public health problem in developing countries like Ethiopia. The risk of dying from NCDs in low and lower-middle-income countries is almost two times that in high-income countries. NCDs account for 42% of deaths in Ethiopia. The trend of deaths due to NCD is increasing over time in Ethiopia. The objective of this study was to assess the magnitude of metabolic syndrome and its components among adult residents of Mekelle city.Method: a community-based cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…This shows a high burden of unapparent illness related to central obesity which increases the risk of a consequent problem. The prevalence of central obesity reported in this study was higher than the results of the study conducted in Ethiopia, like northwest Gondar, 15 Addis Ababa, 16 Dila, 17 Mekelle, 18 India, 46 Eastern Sudan, 47 Tanzania, 48 Uganda, 49 West Africa, 50 southeastern Nigeria 51 Spain, 52 South China, 53 and North China. 54 This finding is in line with a study done in Northwestern Iran, 55 the possible justification for these discrepancies might be attributed to the sociodemographic difference of the study population.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This shows a high burden of unapparent illness related to central obesity which increases the risk of a consequent problem. The prevalence of central obesity reported in this study was higher than the results of the study conducted in Ethiopia, like northwest Gondar, 15 Addis Ababa, 16 Dila, 17 Mekelle, 18 India, 46 Eastern Sudan, 47 Tanzania, 48 Uganda, 49 West Africa, 50 southeastern Nigeria 51 Spain, 52 South China, 53 and North China. 54 This finding is in line with a study done in Northwestern Iran, 55 the possible justification for these discrepancies might be attributed to the sociodemographic difference of the study population.…”
Section: Discussioncontrasting
confidence: 81%
“…Of these variables, age, sex, marital status, Alcohol Consumption, watching television, and physical activities were statistically significant in multivariate analysis at p <0.05 ( Table 2 ). The results of multivariable logistic regression analysis:- age above 45 years, were 3.75 times more likely to be centrally obese than those younger 18–29 age [AOR=3.75, 95% CI (1.86,7.55)], female participants were 2.52 times more likely to be centrally obese than males [AOR=2.52, 95% CI (1.62, 3.94)], participants who consumed alcohol are 2.61 times more likely to be centrally obese than who do not consume alcohol [(AOR=2.61,95% CI (1.68, 4.05)]. Marital status, being married were 2.07 times more likely to develop centrally obese as compared to single [(AOR=2.07,95% CI (1.23, 3.49), Physically inactive individuals were 2.05 times more likely to have central obesity than physically active [AOR=2.05,95% CI (1.23, 3.42)].…”
Section: Resultsmentioning
confidence: 98%
“…The prevalence of MetS was estimated based on the IDF and NCEP/ATPIII criteria among the Ethiopian population of various study subjects. Fourteen studies reported the prevalence of MetS based on both IDF and NCEP/ATPIII criteria [ 36 – 44 , 48 50 , 54 , 56 ], seven studies based on NCEP/ATPIII criteria only [ 57 – 63 ], and again seven studies by IDF criteria only [ 45 47 , 51 53 , 55 ]. Table 3 presents the characteristics and outcomes of the reviewed studies.…”
Section: Resultsmentioning
confidence: 99%